Small cell discovery based on TOA fingerprint database - Yang CHEN; Zhenzhu LEI; Bin SHEN (Dianxin kexue)
In the scenario that a large number of small cells are deployed in the mobile communication network,the number of carriers to be detected by the user equipment (UE) in inter-frequency scanning is considerably larger than that in the conventional network deployment scenarios.This procedure may consume tremendous amounts of UEs’ energy.In order to solve this problem,a small cell discovery (SCD) scheme based on TOA fingerprint database to alleviate intensive energy consumption was proposed when the UEs try to find their potential serving small cells.The proposed scheme reduces the energy consumption of the UE by decreasing the number of unnecessary inter-frequency detection.The simulation results verifiy that the proposed scheme,compared with the existing SCD strategy using received signal strength (RSSI) based radio maps,has better anti-noise performance and higher accuracy.In addition,it can effectively help the high-speed UE avoid performing inter-frequency detection,and hence increase the rate of the UE being successfully connected to the appropriate small cell.